Cost-effectiveness of bivalent, quadrivalent, and nonavalent HPV vaccination in South Africa - Michaeli, Daniel; Stoycheva, Sophia; Marcus, Simon Mashudu; Zhang, Wenjia; Michaeli, Julia; Michaeli, Christoph T. (Clinical drug investigation, 2022)
In South Africa, the prevalence of human papillomavirus (HPV) and associated diseases, such as cervical cancer and genital warts, is among the highest in the world. This study evaluates the cost-effectiveness of bivalent, quadrivalent, and nonavalent HPV vaccination for 9- to 14-year-old girls from the South African healthcare system perspective.